The (In)frequency of the Name ‘Erastus’ in Antiquity: A Literary, Papyrological, and Epigraphical Catalog - Brookins, Timothy (New Testament studies, 2013)
Three questions have remained central to the Erastus debate (Ἔραστος ὁ οἰκονόμος τῆς πόλɛως, Rom 16.23): the date of IKorinthKent 232, the nature of the office of οἰκονόμος (τῆς πόλɛως), and the frequency of the name ‘Erastus’ in antiquity. The present article focuses on the third issue. Moving beyond Meggitt's earlier research (1996, 1999), the author here furnishes a comprehensive catalog of literary, papyrological, and epigraphical occurrences of the name (in Greek and in Latin) in antiquity. The chief payoff of the catalog is two-fold: (1) it provides, for the first time, comprehensive quantitative evidence that the name was in fact rare; and (2) it reveals a significant dearth of attestations from first-century Greece.